Antinuclear antibody levels in Polymorphic Light Eruption and their relation to the severity of disease - Iffat Hassan; Peerzada Sajad; Sabiya Majid; Hamid Bashir (Our Dermatology Online, 2012)
Introduction: PLE is an idiopathic photodermatosis characterised by a polymorphic eruption ranging from papulo-vesicular lesions to large plaques, located predominantly in a photoexposed distribution. It is an acquired disease and is the most common idiopathic photodermatosis. It is characterised by recurrent abnormal delayed reaction to sunlight. PLE is the most common idiopathic photodermatosis, the prevalence of which has been estimated to be around 10-20% in USA, England and Ireland. Previous studies have shown elevated levels of ANA in 2.9-19% of patients with PLE. Aim: The aim of our study was to determine the frequency of ANA positivity in a cohort of patients of ethnic kashmiri origin with Polymorphic light eruption and to examine whether there is any relation of their levels with the severity of disease.Methods: Patients with Polymorphic light eruption clinically who attended the Outpatient Deptt. of Dermatology GMC Srinagar were referred to the Deptt. of Biochemistry GMC Srinagar where patients blood samples were analysed for ANA index by ELISA method (BRIO SEAC ITALY).Results: Our study consisted of 36 patients (with 23 males and 13 females with age group ranging between 15-65 years) presenting with typical clinical features of PLE without associated autoimmune connected tissue diseases like discoid lupus erythematosus or systemic lupus erythematosus and 20 healthy age and sex matched controls. Two patients (1 male and 1female) showed positive results and 1 patient (female) showed equivocal results. Among the control group one patient showed ANA positivity. Thus total frequency of ANA positivity of of 5.55% was observed among the cases and 5% among the controls with frequency of 4.34% in males and 7.69% in females.Conclusion: ANA levels were found in 5.55% of patients with PLE, however there is no relation between the levels of ANA in PLE and with the severity of disease (p value >0.05).